Estudo da injeção de solvente frio no processo de drenagem gravitacional assistida com vapor e solvente (ES-SAGD) em reservatórios do nordeste brasileiro - Praxedes, Tayllandya Suelly (2018)
The number of heavy oil or bitumen reservoirs in the world is large. This oil has high viscosity and thus difficult mobility within the reservoir. In Brazil, the state of Rio Grande do Norte stands out, which has a long production of heavy oil through onshore wells. Through heating, the thermal methods reduce the viscosity of this oil, facilitating its extraction. Among the thermal methods, assisted gravitational drainage with steam and solvent (ES-SAGD) is a promising alternative for the recovery of heavy oil. ES-SAGD combines the advantages of the thermal method with the miscible, and has been successfully tested especially in Canada, where there are many reservoirs of bitumen and heavy oil. This process uses two parallel horizontal wells, where the upper one injects steam and solvent and the lower one produces the oil. The ES-SAGD has not yet been applied in Brazil, where there are heavy oil reservoirs, especially in the Brazilian Northeast. Based on this context, this research aimed to study the application of the ES-SAGD process in a semisynthetic reservoir, with characteristics similar to those found in the Brazilian Northeast, specifically to analyze the influence of the solvent injection scheme on ES-SAGD. The models studied considered the load and heat losses in the injector well and the numerical simulations were carried out through the CMG (Computer Modeling Group) STARS thermal simulator. Some operational parameters were analyzed, such as: steam injection rate, percentage of solvent injected and vertical distance between the wells, in order to verify the influence of these on the ES-SAGD in both configurations: solvent injected in the temperature of the vapor (inj_q) or in the temperature of the reservoir (inj_f). An analysis of NPV (Net Present Value) was also performed, from which the sensitivity of economic parameters was investigated. For the cases studied it was found that the ES-SAGD process with steam injection in conjunction with cold solvent proved to be feasible and recommended both from a technical and economical point of view and from the point of view of safety of the process, since it suppresses the heating step of the solvent, thus eliminating imminent risks of explosions and accidents arising from the rise in solvent temperature.